The role of WNT and IL-1 signaling in osteoarthritis: therapeutic implications for platelet-rich plasma therapy - Tonutti, Antonio; Granata, Valentina; Marrella, Veronica; Sobacchi, Cristina; Ragusa, Rita; Sconza, Cristiano; Rani, Nicola; Di Matteo, Berardo; Ceribelli, Angela (Frontiers in Aging, 2023)
Different from inflammatory arthritis, where biologicals and targeted synthetic molecules have revolutionized the disease course, no drug has demonstrated a disease modifying activity in osteoarthritis, which remains one of the most common causes of disability and chronic pain worldwide. The pharmacological therapy of osteoarthritis is mainly directed towards symptom and pain relief, and joint replacement is still the only curative strategy. Elucidating the disease pathophysiology is essential to understand which mechanisms can be targeted by innovative therapies. It has extensively been demonstrated that aberrant WNT and IL-1 signaling pathways are responsible for cartilage degeneration, impaired chondrocyte metabolism and differentiation, increased extracellular matrix degradation, and altered subchondral bone homeostasis. Platelet-rich plasma is an autologous blood derivative containing a concentration of platelets that is much higher than the whole blood counterpart and has shown promising results in the treatment of early knee osteoarthritis. Among the proposed mechanisms, the modulation of WNT and IL-1 pathways is of paramount importance and is herein reviewed in light of the proposed regenerative approaches.